Disruption of glutamate neurotransmitter transmission is modulated by SNAP-25 in benzo[a]pyrene-induced neurotoxic effects. (1st June 2017) - Yang, Kai; Jiang, Xuejun; Su, Qiuping; Wang, Jing; Li, Chunlin; Xia, Yinyin; Cheng, Shuqun; Qin, Qizhong; Cao, Xianqing; Chen, Chengzhi; Tu, Baijie
Abstract: Benzo[a]pyrene (B[a]P), a ubiquitous chemical contaminant in the environment, is a well-established neurotoxicant to human. However, the molecular mechanisms for B[a]P neurotoxicity are still unclear. In the present study, after treating Sprague-Dawley rats with 0.02, 0.2 and 2.0 mg/kg/day B[a]P for 7 weeks [from postnatal day (PND) 5 to PND54], our results showed that B[a]P exposure caused a significant deficits in learning and memory function. By using U87 cells as in vitro model, the significant cytotoxicity and the induction of apoptosis caused by B[a]P were further verified. More importantly, we demonstrated for the first time that B[a]P exposure caused the disruption of glutamate (Glu) neurotransmitter transmission by decreasing the level of Glu, reducing the expression of Glu receptors (GluR1 and GluR2), enhancing the level of SNAP-25, widening the synaptic cleft, and ultimately producing the neurotoxic effects in both cells and animals. Our results will provide novel evidence to reveal the possible role of SNAP-25 in B[a]P-induced neurotoxicity and may be helpful for searching the potential strategy for the prevention measures against B[a]P neurotoxicity.